Quantifying matrix-fiber mechanical interactions in hyperelastic materials. (1st April 2021) - Mansouri, M.R.; Beter, J.; Fuchs, P.F.; Schrittesser, B.; Pinter, G.
Highlights: The matrix-fiber mechanical interactions are quantified using a combined experimental, analytical, and simulation study. A comprehensive set of experimental data is provided. The matrix-fiber interaction is introduced as an underlying mechanism contributing to the flexible composites. Graphical abstract: Image, graphical abstract Abstract: Hyperelastic fiber-reinforced materials are commonly characterized and modeled in terms of the contributions of the constituent materials, while their matrix-fiber mechanical interactions have been received little attention. This work is an initial attempt to quantify the matrix-fiber mechanical interactions using a combined experimental, analytical, and simulation study. For the experiments, the local stretch maps are captured via digital image correlation during tensile tests on polydimethylsiloxane-glass fiber (PDMS-GF) and polyurethane-glass fiber (PUR-GF) composites with different aspect ratios and various material anisotropy. Moreover, in situ optical measurements during mechanical loadings are carried out on transparent PDMS-GF composites to monitor the change of angle between deformed fibers, as the origin of the matrix-fiber interactions. The stress-stretch responses of all composite materials are then presented, showing different behaviors based on the sample aspect ratios for a specific material anisotropy. The analytical study is carried out within a constitutive framework by adapting a matrix-fiber-interaction model proposed for the modeling of mechanical interactions. The constitutive framework, including an angular-base invariant, a specific deformation gradient, and the stress-stretch behavior of the model, is compared against the experimental results. An FE-implementation using user-defined subroutines is presented, which allows us to perform a combined experimental and simulation study of the matrix-fiber mechanical interactions. Finally, the underlying mechanism contributing to the mechanical behavior of hyperelastic fiber-reinforced materials is discussed via performing a couple of finite element analysis.